2020
DOI: 10.3390/su12176993
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between E-Commerce and Firm Performance: The Mediating Role of Internet Sales Channels

Abstract: This paper postulates that the effect of e-commerce on firm performance is not direct and needs to be examined using mediating factors. The Ordinary Least-Squares (OLS) model was employed with the data of the Flash Eurobarometer 439 Survey entitled The Use of Online Marketplaces and Search Engines by small and medium enterprises. The obtained findings provide support for the mediating hypothesis. To be more precise, while the relationship between e-commerce and firm performance is negative, it is positively me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 56 publications
0
42
0
1
Order By: Relevance
“…The study both strengthens and extends the application of this theory in the IS literature by explaining how e-business capabilities can be considered important resources to further organizational performance. Accordingly, the current study investigated the three individual e-business processes as notable capabilities to provide a better scholarly understanding of their importance, respectively, rather than considering them as a single process ( Saeed et al, 2005 ; Šaković Jovanović et al, 2020 ). Similarly, while extant literature could only educate us on the importance of e-business entity as a whole (e.g., Rai and Tang, 2010 ), the current study offers a deeper understanding of how online capabilities related to suppliers, distributors, and customers can help leverage organizational performance.…”
Section: Methodsmentioning
confidence: 99%
“…The study both strengthens and extends the application of this theory in the IS literature by explaining how e-business capabilities can be considered important resources to further organizational performance. Accordingly, the current study investigated the three individual e-business processes as notable capabilities to provide a better scholarly understanding of their importance, respectively, rather than considering them as a single process ( Saeed et al, 2005 ; Šaković Jovanović et al, 2020 ). Similarly, while extant literature could only educate us on the importance of e-business entity as a whole (e.g., Rai and Tang, 2010 ), the current study offers a deeper understanding of how online capabilities related to suppliers, distributors, and customers can help leverage organizational performance.…”
Section: Methodsmentioning
confidence: 99%
“…From the Flash Eurobarometer 439 Survey in 2017 on 863 companies, Šaković-Jovanović et al [18] found that the effect of e-commerce on enterprise performance is not direct and needs to be examined using several mediating factors. The results showed that, the relationship between e-commerce and sales performance is generally negative, but the benefits of e-commerce to increase sales were more evident when companies used commercial sites and online marketplaces.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The studies [43,54] analyzed ICT fields and sectors that would be very positively influenced by growth of e-commerce, that would have direct impact on increased labor force occupation and would be specialised in: maintenance, hardware support, software development, web design and programming, database and network administrators, computer operators and connected fields of expertise, sales workers, business managers, negotiators, and so on. According to [54,55], most of the companies that are easily adaptable developing e-commerce and stimulating employment growth in this sector are the small and medium enterprises. The labour force analysis [56] for the retail industry in 35 European countries over a 10-year timeframe (2007-2016) shows the negative influence of the total revenue of e-commerce companies on labour force occupation for the retail commerce sector.…”
Section: The Influence Of E-commerce On Employment Ratementioning
confidence: 99%
“…The labour force analysis [56] for the retail industry in 35 European countries over a 10-year timeframe (2007-2016) shows the negative influence of the total revenue of e-commerce companies on labour force occupation for the retail commerce sector. Together with the strong development of e-commerce, with its acceptance by customers and suppliers, the sales volume and the number of available jobs have increased after 2016 and that has determined its direct impact on jobs growth [55,56].…”
Section: The Influence Of E-commerce On Employment Ratementioning
confidence: 99%